Renal angioplasty and stenting: long-term results and the potential role of protection devices. (March 2005) - Henry, Michel; Henry, Isabelle; Polydorou, Antonio; Rajagopal, Sriram; Lakshmi, Gopalakrishnan; Hugel, Michèèle
Renal angioplasty and stenting have become the first treatments to be proposed to patients presenting with renal artery stenosis. The immediate technical success rate is high, with a low complication rate and good long-term patency. In most reports, renal stenting has been proven to improve blood pressure. However, despite good immediate- and long-term results, postprocedural deterioration of renal function is a concern, and may occur after renal artery angioplasty and stenting in 20 to 40% of patients, which limits the immediate benefits of this technique. Of the causes of this deterioration in renal function, atheroembolism seems to play an important role. Contrary to earlier beliefs that atheroembolization is not an issue during percutaneous catheter interventions, there is now mounting evidence that distal atherosclerotic debris commonly embolizes from lesions in many vascular territories during percutaneous interventions. Atheroembolism seems to be the root cause of many procedural complications wherever atherosclerotic lesions are treated. Distal embolization was first demonstrated in saphenous vein grafts and now, clinical data are proving that similar embolization and distal-organ complications also occur during catheter treatment in certain native coronary lesions, carotid stenting and renal artery stenting, demonstrating the role and efficacy of protection devices to reduce the incidence of end-organ complications. The same protection devices (protection balloon and filters) utilized for coronary or carotid procedures may be used to protect the kidney from atheroembolism. In this review, the authors discuss recently published data concerning the techniques and results of renal angioplasty and stenting procedures performed under protection, and evaluate the benefits of this technique on renal function and its role in the future. Indications for this technique need to be discussed.